Pengaruh Content Marketing dan Electronic Word Of Mouth (E-WOM) pada Media Sosial Tiktok Terhadap Keputusan Pembelian Produk Wardah - Fatya Nisa Salsabila; Iwan Subandi (Jurnal Manajemen Bisnis Digital Terkini, 2025)
The development of digital technology has changed consumer interaction and behavior patterns, including in purchasing decisions. Social media, especially TikTok, has become a strategic platform in marketing due to its interactive and visual content-based nature. Wardah, as a local cosmetics brand, utilizes TikTok through content marketing and Electronic Word of Mouth (E-WOM) strategies to strengthen brand awareness and encourage purchasing interest. This study aims to analyze the influence of content marketing and E-WOM on TikTok social media on the decision to purchase Wardah products. The research method used is quantitative with an associative approach. The research sample consisted of 97 respondents determined through purposive sampling. Data analysis was conducted using validity and reliability tests, descriptive analysis, classical assumption tests, hypothesis testing, multiple linear regression analysis, and the coefficient of determination R2. The results showed that content marketing had a positive and significant effect on purchasing decisions (t-count = 2.188; sig. 0.031). E-WOM also has a positive and significant effect (t-count = 15.020; sig. 0.001), with a more dominant effect than content marketing. Simultaneously, both social media have a significant effect on purchasing decisions (F-count = 119.690; sig. 0.001). The coefficient of determination (R²) of 0.718 indicates that 71.8% of the variation in purchasing decisions can be explained by both social factors, while 28.2% is influenced by other social factors outside the scope of this study. These findings confirm the importance of digital marketing strategies based on creative content and consumer reviews in increasing purchasing decisions for Wardah products on TikTok.